COVID-19 Vaccines: Community Myths Vs Facts - Abbas, Syed Waqar; Zareen, Syeda Fatimah; Nisar, Shazia; Farooq, Aliya; Rasheed, Abdul; Saleem, Muhammad Umer (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the reasons for hesitancy regarding COVID-19 vaccines. Study Design: Cross-sectional study. Place and Duration of Study: Combined Military Hospital, Rawalpindi Pakistan, from Feb to Jun 2021. Methodology: After Ethical Committee approval, 100 respondents were recruited, regardless of vaccination status, and requested to respond to 27 different myths and queries circulating about COVID-19 vaccines. Results: Mean age of participants was 36.25 ± 5.77 years, ranging from 15-80 years. Fifty-three were males and 47 females. 41% of subjects trusted the Sino-pharm vaccine, and 25% preferred Pfizer Bio N Tech, while 34% could not answer due to the lack of knowledge. 55% subjects showed concern about catching the infection from Vaccination. 54% considered vaccines unsafe for pregnant and breastfeeding women. 29% believed it unsafe for the elderly and those with comorbidities. 14% believed it could cause autism in children and infertility in adults. 62% individuals acknowledged that vaccines have no nano chips to track patients. 46% opined that vaccines were rushed through trials and had doubtful efficacy. 11% individuals thought vaccines could alter DNA, while most were aware of this false concept. 28% considered that vaccines were needless because recovery from COVID-19 was excellent, while 63% emphasised the need for Vaccination. 23% deemed the side effects of vaccines more dangerous than the disease itself. 85% individuals favoured use of mask and social distancing after getting the vaccine. Conclusion: Strong efforts are needed to support the COVID-19 vaccine and to eliminate negative propaganda on media outlets.